Perancangan Website Sebagai Media Informasi Dan Promosi Sewa Mobil Rico Travel Mandiri - Amanda Paradita Adha; Wulan Nofita Ningsih; Sularno Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
A website is one of the most effective media for providing information and promoting a product or service. Rico Travel Mandiri is a car rental business located in Sijunjung Regency that offers a variety of vehicles at affordable prices and professional service. However, the promotion and booking process was previously carried out manually through social media and direct communication. The purpose of this research is to design a website as an information and promotion medium that facilitates customer bookings and helps the business expand its marketing reach. The development method used is the Extreme Programming (XP) method, consisting of planning, design, coding, and testing stages. Data were collected through observation, interviews, and literature studies. The results show that the designed website can display fleet information, rental rates, booking forms, and contact pages interactively. This website is expected to improve promotional efficiency and customer service at Rico Travel Mandiri.